Do Social Media Marketing Activities Enhance Customer Satisfaction and Co-Creation - Indra Listyarti; Tatik Suryani; Faza Faikar Cordova (Asian Journal of Business and Accounting, 2023)
Manuscript type: Research paper Research aims: The main objective of this research is to examine the role of Social Media Marketing Activities (SMMA) in enhancing customer satisfaction and co-creation of local brands from the Schematic Perspective Theory. Specifically, this research aims to analyse the effect of SMMA on brand awareness and brand image, and the impact of brand image on customer satisfaction and customer co-creation. Design/Methodology/Approach: This research was designed with a survey method which involved 316 respondents, and the data was analysed using partial least squares structural equation modeling, with the WarpPLS 7.0 software. Research findings: The findings indicated that the effect of SMMA is positively significant on customer brand awareness and brand image. And brand image, in turn, has a positively significant effect on satisfaction, and satisfaction has an impact on customer co-creation. This research also found that satisfaction has an important role in mediation, that also stimulates customer co-creation. Theoretical contribution/Originality: This study theoretically contributes to the relationship between customer satisfaction and co-creation in the context of SMMA, based on Schematic Perspective Theory and Social Exchange Theory (SET). However, the research focus on SET on the effect of customer satisfaction on customer co-creation is secondary. Practitioner/Policy implications: The implication of this research is very important for companies to design their own SMMA based on interactivity and customisation attributes. Customer satisfaction is a necessary condition for enhancing customer co-creation. Research limitation/Implications: To enhance the understanding of the complex relationship among the variables, we suggest examining the effects of SMMA directly on customer satisfaction, and the possibility of reciprocal relationship between customer satisfaction and customer co-creation.